Non-destructive testing principles and accurate evaluation of the hydraulic measure impact range using the DC method. (10th November 2017) - Qiu, Liming; Shen, Rongxi; Song, Dazhao; Wang, Enyuan; Liu, Zhentang; Niu, Yue; Jia, Haishan; Xia, Shankui; Zheng, Xiangxin
Abstract: An accurate and non-destructive evaluation method for the hydraulic measure impact range in coal seams is urgently needed. Aiming at the application demands, a theoretical study and field test are presented using the direct current (DC) method to evaluate the impact range of coal seam hydraulic measures. We firstly analyzed the law of the apparent resistivity response of an abnormal conductive zone in a coal seam, and then investigated the principle of non-destructive testing of the coal seam hydraulic measure impact range using the DC method, and used an accurate evaluation method based on the apparent resistivity cloud chart. Finally, taking hydraulic fracturing and hydraulic flushing as examples, field experiments were carried out in coal mines to evaluate the impact ranges. The results showed that: (1) in the process of hydraulic fracturing, coal conductivity was enhanced by high-pressure water in the coal seam, and after hydraulic fracturing, the boundary of the apparent resistivity decrease area was the boundary impact range. (2) In the process of hydraulic flushing, coal conductivity was reduced by holes and cracks in the coal seam, and after hydraulic flushing, the boundary of the apparent resistivity increase area was the boundary impact range. (3) After the implementation of the hydraulic measures, there may be some blind zones in the coal seam; in hydraulic fracturing blind zones, the apparent resistivity increased or stayed constant, while in hydraulic flushing blind zones, the apparent resistivity decreased or stayed constant. The DC method realized a comprehensive and non-destructive evaluation of the impact range of the hydraulic measures, and greatly reduced the time and cost of evaluation.